The Education for Gender Equality and Human Rights in Indonesia: Contemporary Issues and Controversial Problems - Larasati, Ayu Maulidina; Ayu, Novia Puspa (Faculty of Law Universitas Negeri Semarang, 2020)
This paper is motivated by the many legal issues concerning human rights issues that occur in the Indonesian education sector, especially regarding gender discrimination. Gender is the differentiation of roles, functions and responsibilities between women and men resulting from socio-cultural construction and can change according to the times. This paper discusses the main issues of gender in the perspective of human rights and gender equality education in Indonesia. Gender is a gender difference that is not caused by biological differences and not God's nature, but was created by both men and women through a long socio-cultural process. Differentiating the roles, functions and responsibilities of men and women in this social context is basically not a problem, but when examined more deeply it can be a cause of the emergence of gender discrimination, which is one of the sexes whose basic rights are neglected, left behind and experiencing problems of injustice.